SET OF ORGANIZATIONALLY-DIDACTIC CONDITIONS OF THE MODEL OF STUDENTS’ AUTONOMY DEVELOPMENT SYSTEM IMPLEMENTATION - Roman A. Popov (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The model of the autonomy development system gains efficacy due to the fulfillment of certain conditions, both organizational and didactic – in other words, of those conditions, which are directly related to the educational process changes, modernization of the organizational forms, strategies of the educational content mastery, etc. National scholars use the word combination “organizationally-didactic conditions” which mainly reflects the peculiarities of the internal organization, positioning and correlation of the leading methodological approaches, methods, techniques, practices, peculiarities of the educational process structuring, etc., aimed at the solution of a certain scientific problem. The implementation of the model of the autonomy development system will be efficient due to the fulfillment of the following organizational-didactic conditions: usage of the mechanisms for the didactic structuring of the educational information content for its autonomous intake by students; application of versatile interdisciplinary relations within the model of the higher educational institution students’ autonomy development system; didactic synthesis, correlation and clustering of educational assignments; complementarity of the autonomous and non-autonomous forms of activity; students’ professional self-development and self-actualization within the process of autonomous activeness. The first organizational-didactic condition is usage of the mechanisms for the didactic structuring of the educational information content for its autonomous intake by students. Work over the logical structure of the educational information in autonomous educational activities is the central task of a pedagogue, who strives to create conditions, stimulating professional activeness. Including into the autonomous educational activities structural logical schemes; values-oriented exercises; creative work based upon the choice mechanism; cognitive situation-specific tasks, whose solution procedure is constructed according to the increase of the comprehensiveness; problematicity; novelty; interdisciplinary relations and creativity secures the achievement of positive result in the process of autonomy formation. Due to this kind of activity the emotion-value oriented perception begins to lead the consciousness; students comprehend the importance of the basic, fundamental professional values and start following them in their everyday lives, seek to resist negative developments. Application of versatile interdisciplinary relations within the model of the higher educational institution students’ autonomy development system is the second organizational-didactic condition. It is at the higher school that the sharp increase of educational-cognitive activeness is observed; students actively absorb new humanitarian concepts of interdisciplinary content (from social studies, cultural sciences, literature studies, etc.) along with mastering the complex of educationalcognitive actions and skills. Interdisciplinary relations envisage mutual systematic coherence: the content of education on different subjects, selection of educational material, its construction from the perspective of the general aims of education and specifics of each subject. Along with that, the interdisciplinary relations are based upon the intrasubject consequence of educational subjects and on the methods of these subjects’ learning. We consider the didactic synthesis, correlation and clustering of educational assignments as an important organizationally-didactic condition. It is this condition that fosters the formation of a widely educated person with well-developed associative thinking, able to apply non-conventional approaches to resolve different problems. Didactic synthesis and correlation of educational information allows performing the educational process at a high difficulty level. Didactic synthesis and correlation are not only to be conducted with relation to the tasks of a certain training course, but also in relation to the tasks of different related courses. The next organizational-didactic condition of students’ autonomy development – complementarity of the autonomous and non-autonomous forms of activity – logically emerges from the principles of autonomy development. We consider as the core for the activation of the potential of versatile disciplines the unity of the content of education at a higher school, commonness and complementarity (transfusion and mutual supplement) of the requirements, principles, components and means for the implementation of the sense of education. The complementarity of the autonomous and non-autonomous forms of activity is reached through the automation of the general education skills and abilities. The idea of the complementarity of the autonomous and non-autonomous forms of activity can find its full implementation due to the application of informational and communicative means. Professional self-development and self-actualization in the process of autonomous activity is the last organizational-didactic condition of the implementation of the model of the autonomy development system. The categories of self-identification and self-esteem are closely related to the phenomena of the formation of the professional self-consciousness of a future specialist and professional self-respect. The category of professional self-consciousness has the morphogenetic role in the self-identification and professional self-actualization on the background of the general professional formation. During their professional trainings, students consciously or unconsciously capture their satisfaction or dissatisfaction with themselves and their behavior, self-confidence, or self-doubt due to which their comprehensive Self-concept is formed – self-confidence (or selfdoubt), ability (inability) to overcome an unpredicted situation. We interpret the value-based area of professional training as a favorable alternative to the educational and awareness-building paradigm of higher education which so far dominates in the national educational field.